Effect of aspect ratio variation on subsonic aerodynamics of cascade type grid fin at different gap-to-chord ratios. (3rd April 2020) - Tripathi, M.; Sucheendran, M.M.; Misra, A.
ABSTRACT: This paper dwells upon investigating the effect of aspect ratio ( AR ) variation on the aerodynamic performance of unconventional control surfaces called grid fins by virtue of a series of subsonic experiments on a simplified grid fin variant called the cascade fin. Wind tunnel tests were performed for different AR (variable span) grid fins. The same had been investigated for different gap-to-chord ratio ( g / c ) variants. Results demonstrated a tangible increase in the aerodynamic efficiency as well as stall angle reduction for higher AR . Moreover, higher AR leads to increased pitching moment, which emphasizes elevated hinge moment requirements. The study ensued the presence of higher deviation between the low AR fins, that is AR<2 compared to the pertinent deviations between the high AR fins, that is AR≥2 . The effect associated with these variations was termed as span effect in this paper. It was established that, the deviations arising due to this phenomena were lesser for higher g / c and higher AR . The analysis of AR variation for different g / c presented a limiting value of AR reduction for stall performance enhancement. Thus, optimised selection of the g / c and AR values can lead to enhanced aerodynamic efficiency alongside an improved stalling characteristic.